Hubungan Antara Sikap dan Dukungan Suami dengan Praktik Pemberian ASI Eksklusif pada Ibu tidak Bekerja yang mempunyai Bayi 7-12 Bulan di Wilayah Kerja Puskesmas Ngemplak SImongan Kecamatan - Yuyun Dwi Kohariningsih; Ngadiyono Ngadiyono (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
UNICEF states in order to reduce infant mortality in Indonesia and deaths of children under five in the world each year could be prevented through exclusive breastfeeding for 6 months, in Indonesia the policy set out in the Decree of the Minister of Health No.450/Menkes/SK/IV/2004. Indonesia has a target SPM of 80% but in Central Java is still very difficult to reach that number, in Semarang coverage of exclusive breastfeeding rate in 2011 only was 21.16%, and one of them at the Ngemplak Simongan health center in 2011 E0-E6 19.20 %. The purpose of this research is